Weather Signs - Chappell, Rachel; Nang Chan Yeema (Bethany, MO USA Fitzgerald Books, 2007)
Illustrations and text introduce weather lore - old sayings based on weather signs, from rainbows and dew, to cloud signs, black smoke, fish, and more.
Keywords: Juvenile Nonfiction